2020
DOI: 10.5799/jcei/8211
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and Fertility in the Time of COVID-19

Abstract: COVID-19 is an acute respiratory disease caused by novel coronavirus SARS-CoV-2 or 2019-nCoV. Recently, on March 11, 2020, COVID-19 was declared by the WHO as a virus pandemic disease. Many measures were conducted to tackle COVID-19 outbreak. The important one is social isolation that have been adopted all over the world which are the first one done as widely as that in modern history. Such measures have wide reaching consequences as reducing significantly the opportunity for casual sexual meetings, and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In domestic COVID-19 isolation, couples are less distracted, have more time for each other, and can indulge in love making more often during the day, which—planned or unplanned—will inevitably lead to a “coronavirus baby boom” in nine months. This is at least a description found in mass media contributions (Döring & Walter, 2020 ) and academic papers (Ait Addi et al, 2020 ) alike. The press often speak of “Love in the Time of Corona” (e.g., BBC, 2020 ) in allusion to the bestselling novel “Love in the Time of Cholera” (García Márquez, 1988 ) that tells the story of two lovers who, after a life-long separation, finally get together and use the cholera quarantine on a ship for undisturbed togetherness.…”
Section: Covid-19 Effects On Partnered Sexmentioning
confidence: 61%
See 1 more Smart Citation
“…In domestic COVID-19 isolation, couples are less distracted, have more time for each other, and can indulge in love making more often during the day, which—planned or unplanned—will inevitably lead to a “coronavirus baby boom” in nine months. This is at least a description found in mass media contributions (Döring & Walter, 2020 ) and academic papers (Ait Addi et al, 2020 ) alike. The press often speak of “Love in the Time of Corona” (e.g., BBC, 2020 ) in allusion to the bestselling novel “Love in the Time of Cholera” (García Márquez, 1988 ) that tells the story of two lovers who, after a life-long separation, finally get together and use the cholera quarantine on a ship for undisturbed togetherness.…”
Section: Covid-19 Effects On Partnered Sexmentioning
confidence: 61%
“…Researchers have also begun to address the sexuality-related effects of the COVID-19 pandemic. Comments on different sexuality-related aspects have been published in scientific journals (e.g., Ait Addi, Benksim, & Cherkaoui, 2020 ; Alpalhão & Filipe, 2020 ; Grubbs, 2020 ; Hall et al, 2020 ; Hough, 2020 ; Hussein, 2020 ; Joseph Davey, Bekker, Coates, & Myer, 2020 ; Mestre-Bach, Blycker, & Potenza, 2020 ; Sun et al, 2020 ), as well as first empirical studies (e.g., Chen et al, 2020 ; Jacob et al, 2020 ; Li, Li, Xin, Wang, & Yang, 2020 ; Riley, Sully, Ahmed, & Biddlecom, 2020 ; Sanchez, Zlotorzynska, Rai, & Baral, 2020 ; Yuksel & Ozgor, 2020 ) and research reviews (e.g., Rasmussen, Smulian, Lednicky, Wen, & Jamieson, 2020 ). Scientific societies provide statements on their websites (e.g., ASHA, 2020 ; ISSM, 2020 ; ISSWSH, 2020 ).…”
Section: Sexuality-related Effects Of the Covid-19 Pandemicmentioning
confidence: 99%
“…In present study, the majority of 110 the participants regulated their sexual activity to have children. Other researchers have also reported an increase in the frequency of sexual intercourse among individuals who get the chance to spend more time with their partners at home (Ait- Addi et al, 2020;Döring, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Considering that this situation was frequently caused by the unwillingness of the partner, we may state that the participants had negative attitudes towards contraceptive methods due to sociocultural reasons. Similarly, researchers have concluded that cultural factors affect the acceptance and use of birth control in different ways and are one of the reasons for increasing fertility rates in the COVID-19 pandemic (Ait- Addi et al, 2020;Astratie, 2021). Hence, it is inevitable for unplanned and unwanted pregnancies to increase in pandemic periods.…”
Section: Discussionmentioning
confidence: 99%
“…Some have proposed that with lockdown restrictions and social isolation, there have been fewer opportunities for casual sexual meetings but increased frequency of sexual intercourse among couples in stable sexual relationships [ 50 ]. In a study of 967 young Chinese individuals, due to the COVID-19 pandemic and related containment measures, 22% of participants reported a decrease in sexual desire; 41% experienced a decrease in the sexual intercourse frequency; 30% reported an increase in the frequency of masturbation; 20% reported a decrease in alcohol consumption before or during sexual activities, and 31% reported a deterioration in partner relationships during the pandemic [ 51 ].…”
Section: Introductionmentioning
confidence: 99%